Identification of mycobacterial lectins from genomic data. Issue 4 (24th December 2012) - Abhinav, K. V.; Sharma, Alok; Vijayan, M.
Abstract Sixty‐four sequences containing lectin domains with homologs of known three‐dimensional structure were identified through a search of mycobacterial genomes. They appear to belong to the β‐prism II, the C‐type, the Microcystis virdis (MV), and the β‐trefoil lectin folds. The first three always occur in conjunction with the LysM, the PI‐PLC, and the β‐grasp domains, respectively while mycobacterial β‐trefoil lectins are unaccompanied by any other domain. Thirty heparin binding hemagglutinins (HBHA), already annotated, have also been included in the study although they have no homologs of known three‐dimensional structure. The biological role of HBHA has been well characterized. A comparison between the sequences of the lectin from pathogenic and nonpathogenic mycobacteria provides insights into the carbohydrate binding region of the molecule, but the structure of the molecule is yet to be determined. A reasonable picture of the structural features of other mycobacterial proteins containing one or the other of the four lectin domains can be gleaned through the examination of homologs proteins, although the structure of none of them is available. Their biological role is also yet to be elucidated. The work presented here is among the first steps towards exploring the almost unexplored area of the structural biology of mycobacterial lectins. Proteins 2013. © 2012 Wiley Periodicals, Inc.